Heterodimensional superlattice with in-plane anomalous Hall effect - Zhou, Jiadong (2022)
Superlattices-a periodic stacking of two-dimensional layers of two or more materials-provide a versatile scheme for engineering materials with tailored properties1,2. Here we report an intrinsic heterodimensional superlattice consisting of alternating layers of two-dimensional vanadium disulfide (VS2) and a one-dimensional vanadium sulfide (VS) chain array, deposited directly by chemical vapour deposition. This unique superlattice features an unconventional 1T stacking with a monoclinic unit cell of VS2/VS layers identified by scanning transmission electron microscopy. An unexpected Hall effect, persisting up to 380 kelvin, is observed when the magnetic field is in-plane, a condition under which the Hall effect usually vanishes. The observation of this effect is supported by theoretical calculations, and can be attributed to an unconventional anomalous Hall effect owing to an out-of-plane Berry curvature induced by an in-plane magnetic field, which is related to the one-dimensional VS chain. Our work expands the conventional understanding of superlattices and will stimulate the synthesis of more extraordinary superstructures.